Diabetes care for babies, toddlers, and preschoolers : - Betschart-Roemer, Jean (Chronimed Publising, 1999)
The support you need to manage your little one's diabetes. With your child's diagnosis of diabetes, you may be feeling grief, sadness, or fear. Everything you need to learn to take care of your child's diabetes, in addition to normal parenting issues, can seem overwhelming. You might even worry that you may do something wrong and harm your child. This reassuring guide will help you find a balance between good diabetes management and normal life. It explains how diabetes impacts your child's growth and development, and gives you plenty of ideas for dealing with routine diabetes care.